PENGEMBANGAN RUMAH SAKIT UMUM ISLAM MADINAH DENGAN PENERAPAN HEALING ENVIRONMENT DI KABUPATEN MALANG - Wiwid Lantika Ramdani; Hadi Setyawan; Agus Heru Purnomo (ARSITEKTURA, 2017)
Abstract: Healthcare need in Malang increasing especially on Madinah General Islamic Hospital. The hospital service capacity equivalent to C Class standard Ministry of Health (MoH) today, has not been able to accommodate and handle some of the facilities which include several other specialist medical services, basic sub spesialist medical services also  teeth and mouth specialist medical services. Many patients are referred to the regional hospital which mileage distance far enough, and the lack of the number of patient beds becomes the main establishment background of this project. How spatial meet the needs of all health service activities were comfortable and toward healing environment and in accordance with the rules of Islam. Hospitals with the application of this Healing Environment enabled to answer the needs of people to obtain health care facilities as well as get relief faster. The goal is how to realize the hospital is able to provide health services to the healing process faster and neighborhoods to actively participate in the healing process of patients were able to control the development, including privacy, increasing social support, giving access to a natural and positive distraction else that helps improve medical results. There was established concepts that support healing process: the procurement of green space for higher quality air supply as well as a means of interaction between the patient, the openings which allows patients to access view, optimization of natural lighting and air conditioning, as well as the use of colors and materials that help reduce stress.  Keyword: Healing Environment,Malang, General Hospital